La taxonomie dans la tourmente - Anouk Barberousse; Sarah Samadi (Revue d'anthropologie des connaissances)
Our aim in this paper is to present and discuss the debates both within and without taxonomy. We also expose the solutions that have been proposed to the current crisis of taxonomic expertise. We shed light on the role of genetic data in taxonomic analysis and emphasize the complementarity of genetic data and specimens that are maintained within collections of natural history.